2022
DOI: 10.1007/s12161-022-02415-y
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity Detection of Capsaicin in Red Pepper Oil Based on Reduced Graphene Oxide Enhanced by β-Cyclodextrin

Abstract: Red pepper oil is a kind of condiment used in the food factories, and its spicy degree can be re ected by the content of capsaicin. However, the classi cation method of red pepper oil is too subjective to be applied in food factories. In our work, a sensitivity electrochemical sensor for detecting capsaicin was constructed based on the glassy carbon electrode (GCE) modi ed with β-cyclodextrin (β-CD) assisted reduced graphene oxide (rGO). The results showed that the introduction of β-CD made rGO more dispersed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…From this series, it can be observed that the lowest LODs and the widest dynamic ranges were recorded using β-cyclodextrin reduced graphene oxide polyethylene imine functionalized carbon nanotubes modified glassy carbon electrode (β-CD/ rGO/PEI-CNTs/GCE) and MXene, poly dimethyl diallyl ammonium chloride-carbon nanotubes, and β-cyclodextrin modified glassy carbon electrode (MXene/PDDA-CNTs/β-CD/GCE). [30][31][32][33] For these two sensors, β-cyclodextrin was used to ensure the dispersion of the composite. 32,33 MXene is a type of two-dimensional layered material composed of transition metal nitrides, carbides, or carbonitrides.…”
Section: Electrochemical Sensors Used For the Determination Of Topica...mentioning
confidence: 99%
“…From this series, it can be observed that the lowest LODs and the widest dynamic ranges were recorded using β-cyclodextrin reduced graphene oxide polyethylene imine functionalized carbon nanotubes modified glassy carbon electrode (β-CD/ rGO/PEI-CNTs/GCE) and MXene, poly dimethyl diallyl ammonium chloride-carbon nanotubes, and β-cyclodextrin modified glassy carbon electrode (MXene/PDDA-CNTs/β-CD/GCE). [30][31][32][33] For these two sensors, β-cyclodextrin was used to ensure the dispersion of the composite. 32,33 MXene is a type of two-dimensional layered material composed of transition metal nitrides, carbides, or carbonitrides.…”
Section: Electrochemical Sensors Used For the Determination Of Topica...mentioning
confidence: 99%
“…β-CD was found to have a higher degree of charge transfer. The packaging based on β-CD/rGO/GCE recovered over 94% in the quantification of red pepper oil [146].…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…β-CD was found to have a higher degree of charge transfer. The packaging based on β-CD/rGO/GCE obtained a recovery of over 94% in the quantification of red pepper oil [149].…”
Section: Electrochemical Sensorsmentioning
confidence: 99%